(3TQM GdaGX GOGH GdHMKs - (3eLghds
(3ChdgG (B:s
(3GdMO ef cGTa GSQGQ GdGSQGQ hHYO agPg GdChQGb TGedI Ydi TQM HYV GdCdaGX GdehOYI aj GdQSGdI GdefShHI Edj TeS GdedI GdSeQbfOj aj GOGH GdHMK s
(3BNQgG (B:s
(3hcdeG de JKHJ de jKHJ CUdkG dGf jchf GdNGU NGUkG gPG hdfcJa HgPG GdYOO ef GdeZGdWGJ GdYGeI s
(3Vef eLehY , JQJjHgG (B: 25s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs